Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kepuasan Kerja pada Karyawan PT. Medico Berkat Abadi - Yuzril Ihza Alfani Maulana; Mei Retno Adiwati (BUDGETING : Journal of Business, Management and Accounting, 2023)
The aim of this research is to analyze the direct influence of Work Motivation and Work Discipline on Job Satisfaction in PT Medico Berkat Abadi. The sameple used in this research was employees of PT. Medico Berkat Abadi with total of 60 respondents. This research uses the method. Saturated sampling and analysis techniques usung Partial Least Square. Research result This shows that work Motivation has a significant positive effect on Employee Job Satisfaction and Work Disipline have a significant positive effect on Employee Job Satisfaction. Keyword : Employee Job Satisfaction , Work Discipline, Work Motivation.